2014
DOI: 10.1021/jp5002644
|View full text |Cite
|
Sign up to set email alerts
|

The Entropic Origin of Solvent Effects on the Single Bond cZt-tZt Isomerization Rate Constant of 1,3,5-cis-Hexatriene in Alkane and Alcohol Solvents: A Molecular Dynamics Study

Abstract: The single-bond cZt-tZt isomerization rate constants of 1,3,5-cis-hexatriene dissolved in a series of explicit alkane (cyclohexane, n-heptane, and cycloheptane) and alcohol (methanol, ethanol, and n-propanol) solvents were calculated via reactive flux theory, from classical molecular dynamics simulations, at different temperatures (275-325 K). We find that the isomerization rate constants in alcohol solvents are slower than those in alkane solvents, in accord with the observed experimental trend (Harris, D. A.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 73 publications
(120 reference statements)
0
3
0
Order By: Relevance
“…Under local equilibrium conditions where thermodynamic quantities are defined, the transition state theory relates A to the activation entropy, 53,54 which includes intramolecular as well as solvent (environment) contributions, the latter one being of major influence. [55][56][57][58][59] Recently, the temperature dependence of the excited state lifetimes of a bilin chromophore covalently linked to a structurally heterogeneous phytochrome protein was analyzed similarly to conclude that distinct protein conformers yielded significantly distinct prefactors A. 60 Here, on the one hand the peptide linkage increases the number of intramolecular degrees of freedom, but on the other hand the structural relaxation of the peptide is much slower than the photoisomerization and therefore restricts the accessible volume of the configurational space of the isomerizing subsystem.…”
Section: Resultsmentioning
confidence: 99%
“…Under local equilibrium conditions where thermodynamic quantities are defined, the transition state theory relates A to the activation entropy, 53,54 which includes intramolecular as well as solvent (environment) contributions, the latter one being of major influence. [55][56][57][58][59] Recently, the temperature dependence of the excited state lifetimes of a bilin chromophore covalently linked to a structurally heterogeneous phytochrome protein was analyzed similarly to conclude that distinct protein conformers yielded significantly distinct prefactors A. 60 Here, on the one hand the peptide linkage increases the number of intramolecular degrees of freedom, but on the other hand the structural relaxation of the peptide is much slower than the photoisomerization and therefore restricts the accessible volume of the configurational space of the isomerizing subsystem.…”
Section: Resultsmentioning
confidence: 99%
“…Following the return to the ground state in the femtosecond time scale, those studies found that the time evolution of transient absorption persists in the ps time scale. Due to the large excess of vibrational energy in the nascent 1 1 A species, hot ground state reactions during the first 4–8 ps lead to formation of vibrationally excited higher energy s -cis- conformers whose subsequent relaxation toward the c - and t -Ht all-s- trans conformers occurs in the 100–300 ps time scale. Nondecaying components were attributed to trapping of s- cis -s- trans -conformers of the hexatriene isomers, documented in the Sension study by excess absorption at 272 nm and a bleach at 268 nm . Introducing s- cis -1,3-diene moieties in the hexatrienes moiety shifts the absorption spectrum to the red. Related studies of hot ground state cZc -Ht formation from the photochemical ring opening of 1,3-cyclohexadiene, CHD, and the kinetics of its relaxation to the more stable s -trans -conformers, cZt - and tZt -Ht, were reviewed recently. , Thus, far the shortest excitation pulses, 13 fs, were used by Fuß and co-workers to probe the kinetics of the ring opening of CHD in the gas phase …”
Section: Discussionmentioning
confidence: 99%
“…75−80 Related studies of hot ground state cZc-Ht formation from the photochemical ring opening of 1,3-cyclohexadiene, CHD, and the kinetics of its relaxation to the more stable s-trans-conformers, cZt-and tZt-Ht, were reviewed recently. 81,82 Thus, far the shortest excitation pulses, 13 fs, were used by Fuß and co-workers to probe the kinetics of the ring opening of CHD in the gas phase. 83 Hexatriene Photoisomerization.…”
Section: ■ Introductionmentioning
confidence: 99%